(untitled) (Raparin Journal of Humanities (RJH), 2023)
The failure of Iran’s in the wars against Russia, then the agreement of Gulistan in 1813 and the Treaty of Turkmenchay in 1828 which caused the increase of Russian authority in Iran, according to that agreement Russia got the right to take a number of privileges ،imposition of border agreement and open some consulates. The Russians were able to act as they wished. Iran’s authority didn’t matter much in managing their plans and works, they followed complete independence. Any protest by Iranian officials and senior officials politically and militarily, Russia would have tried to resolve it through bribes and promises. The result of all the wars and agreements between them was just a big loss and fine by Iran, A wide area of Iran become part under Russian control. this left an impact on all sides especially the capitalist law after it was implemented in Iran. The arrival of( Alexander Griboyedoff) as Russian ambassador in the era of Fath- Ali Shah and then killing the ambassador are clear evidence of Russia’s illegal interference in the affairs of that country. Russia was always trying to expand its powers in Iran against its rivals especially Britain. For this reason, whenever getting any privileges by Britain in the same way Russia was trying to get the same privileges. The conflict between Russia and Britain in Iran and their attempts to establish power and more getting their interests were the direct reason for their strengthening and interfering in iran’s internal and external affairs.